2022
DOI: 10.3389/fnut.2022.1038740
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps guangdongensis lipid-lowering formula alleviates fat and lipid accumulation by modulating gut microbiota and short-chain fatty acids in high-fat diet mice

Abstract: Obesity has caused serious health and economic problems in the world. Cordyceps guangdongensis is a high-value macrofungus with broad application potential in the food and bio-medicine industry. This current study aimed to estimate the role of C. guangdongensis lipid-lowering compound formula (CGLC) in regulating fat and lipid accumulation, gut microbiota balance, short-chain fatty acid (SCFA) contents, and expression levels of genes involved in fat and lipid metabolism in high-fat diet (HFD) mice. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Other studies have reported similar benefits from the consumption of ginger, which increased the abundance of Bifidobacterium and SCFA-producing bacteria like Alloprevotella and Allobaculum (Wang et al, 2020). In addition, the Cordyceps guangdongensis lipid-lowering formula regulated the IM and SCFAs, affecting the expression of lipid metabolism-related genes mRNA, such as upregulating Pnliprp1, Pnliprp2, and Ppard, and down-regulating Cidea and Cidec (Wang et al, 2022). Other studies have shown that Huang-Lian-Jie-Du-Decoction improves high blood sugar levels and insulin resistance in rats by increasing SCFAs and antiinflammatory bacteria such as Parabacteroides, Blautia, Akkermansia, and reducing conditional pathogens such as Aerococcus, Staphylococcus, and Corynebacterium (Chen et al, 2018).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 67%
See 1 more Smart Citation
“…Other studies have reported similar benefits from the consumption of ginger, which increased the abundance of Bifidobacterium and SCFA-producing bacteria like Alloprevotella and Allobaculum (Wang et al, 2020). In addition, the Cordyceps guangdongensis lipid-lowering formula regulated the IM and SCFAs, affecting the expression of lipid metabolism-related genes mRNA, such as upregulating Pnliprp1, Pnliprp2, and Ppard, and down-regulating Cidea and Cidec (Wang et al, 2022). Other studies have shown that Huang-Lian-Jie-Du-Decoction improves high blood sugar levels and insulin resistance in rats by increasing SCFAs and antiinflammatory bacteria such as Parabacteroides, Blautia, Akkermansia, and reducing conditional pathogens such as Aerococcus, Staphylococcus, and Corynebacterium (Chen et al, 2018).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 67%
“…At the same time, WEGL can not only reverse the intestinal microbial imbalance induced by HFD, such as the decrease F/B ratio and the level of endotoxin-containing Proteobacteria but also maintain the integrity of the intestinal barrier and alleviate metabolic endotoxemia (Chang et al, 2015). Crocin-I alleviated intestinal microbial diseases, decreased the F/B ratio and the abundance of Proteobacteria, decreased the expression levels of inflammatory cytokines, up-regulated the expression of occludin, Muc1, and Muc2 in colon tissue, increased the levels of SCFAs in the colon, and improved intestinal barrier function and colon tissue inflammation (Xie et al, 2022). In addition, the IM can interact with other organs, such as the liver, brain, and immune system, through various signaling pathways (Anlu et al, 2019).…”
Section: Mucosal Barrier Restoration and Gut-organ Axis Interactionmentioning
confidence: 99%
“…Hypoxia leads to the inhibition of glycolysis and the TCA cycle. To obtain more energy, C. sinensis undergoes anaerobic respiration and accumulates more fatty acid compounds, which are involved in the fatty acid metabolism and synthesis [45,46]. At the same time, it leads to the accumulation of superoxide anions and oxygen-free radicals in C. sinensis.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-treated adzuki SCFAs (98) Inhibits pathways leading to the production of pro-inflammatory cytokines; reduces LPS, thereby reducing chronic low-grade inflammation The TCM compounds can regulate the abundance of gut microbiota and lipid metabolism to treat obesity. In the mechanism involving the regulation of gut microbiota abundance, SCFAs, and genes involved in lipid metabolism, the Cordyceps guangdongensis lipid-lowering formula dramatically reduced weight and fat accumulation in high-fat diet mice (86). By lowering total cholesterol (TC) and triglyceride (TG) levels and increasing the quantity and variety of gut microbiota, the Jian Pi Tiao Gan Yin medicine helps mice with obesity (109).…”
Section: Cordyceps Guangdongensismentioning
confidence: 99%